2004
DOI: 10.1097/01.ccm.0000117317.18092.e4
|View full text |Cite|
|
Sign up to set email alerts
|

Surviving Sepsis Campaign guidelines for management of severe sepsis and septic shock

Abstract: Evidence-based recommendations can be made regarding many aspects of the acute management of sepsis and septic shock that are hoped to translate into improved outcomes for the critically ill patient. The impact of these guidelines will be formally tested and guidelines updated annually and even more rapidly as some important new knowledge becomes as available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
1,977
3
185

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 3,123 publications
(2,186 citation statements)
references
References 126 publications
21
1,977
3
185
Order By: Relevance
“…Table 4) should be rapidly referred to an intensive care unit (ICU) In 2004, the "Surviving Sepsis Campaign" guidelines recommended the use of EGDT [147] based on one large randomized trial [93]. These guidelines were updated in 2008 [148], successively in 2012 [70], and were further supported by several subsequent trials that corroborated the benefit of EGDT in severe sepsis and septic shock [149].…”
Section: The Empirical Treatment Must Be Optimized When Microbiologymentioning
confidence: 99%
“…Table 4) should be rapidly referred to an intensive care unit (ICU) In 2004, the "Surviving Sepsis Campaign" guidelines recommended the use of EGDT [147] based on one large randomized trial [93]. These guidelines were updated in 2008 [148], successively in 2012 [70], and were further supported by several subsequent trials that corroborated the benefit of EGDT in severe sepsis and septic shock [149].…”
Section: The Empirical Treatment Must Be Optimized When Microbiologymentioning
confidence: 99%
“…In the EGDT group, central venous catheterization occurred in only 60 % of the patients at 1 h, in 85 % at 2 h and in 93.6 % at 6 h. Moreover, central venous catheterization occurred in 56.5 and 57.9 % of the patients at 6 h in the other two treatment groups. At last, to be eligible, the study sites had to comply with the Surviving Sepsis Campaign guidelines [5] for non-resuscitation aspects of care. We wonder if these factors might have diluted the treatment differences in the three groups.…”
Section: Question Marksmentioning
confidence: 99%
“…3,4 Based on this evidence, use of IIT to achieve TGC has been advocated to improve outcomes for critically ill patients. 7,8 There have, however, been concerns regarding the broad application of IIT and TGC in critical illness. [9][10][11][12] Specifically, concerns have been raised about the methodology and overall generalizability of the two highest profile IIT trials reported by Van den Berghe et al 3,4 In particular, these trials were both single centre open-label trials where 87% of patients received parenteral nutrition.…”
Section: Commentarymentioning
confidence: 99%